Clinically driven analysis reveals gene-socioeconomic status interaction influencing periodontal disease in the electronic health record-linked Generation Scotland: Scottish Family Health Study (GS: SFHS) cohort. (2018) - Bermingham, Mairead L; Campbell, Archie; Porteous, David; Walls, Angus
No abstract available